IMPLEMENTATION OF AUDIOVISUAL MEDIA IN LEARNING ARABIC MAHARAT AL-ISTIMA’ - Ahmad Faidlullah, Ahmad Faidlullah; Muhammad Afton Ulinnuha (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
Abstract: This study aims to determine the effectiveness of audio-visual media in “maharat al-istima”. To get an understanding of this research, it was carried out using descriptive method and citations from several references because this research tries to describe a growing phenomenon. This method is intended to assess effectiveness. The result of this research is to know the meaning of “maharat al-istima”. So “istima” is a basic human ability that is possessed at the beginning of this birth until throughout his life. But at its level, language learning result in low student learning interest in istima’ learning. The purpose of using audio-visual media is to increase theacher creativity in the learning process in the implementation of istima learning using the audio-visual method has changed the learning atmosphere more interesting and increased student activity in learning. The concept and principle of using visual-media need attention so that the process of using audio-visual media in learning becomes more effective and optimal. Keywords: Audio-Visual Media, Learning Arabic, Maharat al-Istima’ Asbtrak: Penelitian ini bertujuan untuk menjelaskan efektifitas media Audio-visual dalam meningkatkan Maharatul istima’. Penelitian ini dilakukan dengan metode deskriptif dan pengutipan dari beberapa referensi, karena tulisan ini berusaha menggambarkan fenomena yang berkembang. Hasil penelitian tersebut yaitu dapat mengetahui pengertian “maharatul istima’” serta keefektifan penggunaan media audio-visual dalam pembelajaran “maharatul istima’”. Jadi istima’ merupakan kemampuan dasar manusia yang dimiliki pada awal kelahirannya sampai sepanjang hidupnya. Namun pada tatarannya, pembelajaran bahasa terjadi rendahnya minat belajar mahasiswa pada pembelajaran istima’. Tujuan penggunaan media audio-visual adalah untuk meningkatkan inovasi dan kreatifitas guru dalam proses pembelajaran Dalam pelaksanaan pembelajaran istima’ menggunakan metode audio-visual ini telah mengubah suasana pembelajaran lebih menarik dan meningkatkan keaktifan mahasiswa dalam pembelajaran. Konsep dan prinsip penggunaan media-visual perlu diperhatikan, agar proses penggunaan media audio-visual dalam pembelajaran menjadi lebih efektif dan optimal. Kata Kunci: Audio-visual, pembelajaran bahasa Arab, maharatul istima’